Home Base PSPS Dengan Pendekatan Arsitektur Postmodern - Gandhi Thaiba; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Home Base PSPS is the center of facilities owned by PSPS. Home Base PSPS consists of home stadium equipped with various facilities such as, Museum, Cafe, Restaurant, Retail Stores, Kiosk, VIP & VVIP Lounge, the Media Broadcast, and the Press Conference. PSPS Home Stadium is venues that held the match in Indonesia League system. Home Base PSPS design is done with Postmodern Architecture approach and apply the concept of "Hybrid Expression of Rumah Melayu Riau". Application of the theme and concept of this method are integrating Hybrid Postmodern Architecture that combine Art and Science, Craft and Technology, as well as International and Local. The application of the concept for the shape of the building is transformed from the shape of the parts of Rumah Melayu Riau which Riau Culturalist, Alm. Tengku Nasaruddin Effendi described in poem; Yang Bertiang dan Bertangga transformed into concrete columns that have a similar shape with Melayu House; Berdinding penghambat angin dan tempias is transformed on the roof of the Home Stadium which protects 90% of the audience who were in the stands; Berselasar dan berpelatar applied to the skin which is located at the outer facade and not attached to the main building, serves as a barrier also shader for the space next to it; Berselasar dan berpelatar applied to the hall and the court are very broad in order; Bidainya tingkat bertingkat, kaki dan atap berombak-ombak visualized with skin facade structures that crossed and not rigid so that it looks like overlapping and wavy. Home Stadium with a capacity of 32.527 spectators at the Home Base PSPS is present as the appreciation of the people of Riau as the football improving progress in the Earth of Melayu.Key word: Home Base, Hybrid Expression of Rumah Melayu Riau, Postmodern Architecture